Novelties in Randia L. (Gardenieae, Rubiaceae) from Brazil - Borges, Rodrigo Lopes; Roque, Nádia; Jardim, Jomar Gomes; Salas, Roberto Manuel (Phytotaxa, 2024)
Here we publish two novelties in Randia, a description of a new species (R. muricata) and the establishment of R. sulbahiana as a new name for Sphinctanthus insignis. Randia muricata is distinguished by a set of features, such as its muricate fruits, and the discolor venation on abaxial surface of the leaf blades, puberulent. The muricate fruits is an uncommon feature among species in this genus. R. sulbahiana is characterized by the facultative presence of thorns, linear or filiform calyx lobes, and the acute apex of corolla lobes. We provide descriptions, illustrations, figures, an assessment of conservation status, and distribution map of both species. A dichotomous key to distinguish Brazilian’s species of Randia is also provided.